GAMBARAN KESIAPSIAGAAN PADA SUATU RUMAH SAKIT DALAM PENANGGULANGAN BENCANA KEBAKARAN - Citra Aulia Amanda; Adriansyah Arya Pratama, Novita Sari, Abdurrozzaq Hasibuan (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2025)
The aim of this research is to obtain new information and new discoveries. Functions as proof or verification of existing information and as a determinant of hospital preparedness in dealing with fire disasters. This research was conducted as a literature review, with secondary data. The data collection method used in this research is the documentation method. The analytical method used involves analyzing the content of relevant research journals that meet certain criteria, which is then collected and summarized. There are 10 pieces of literature that discuss hospital preparedness in dealing with fire disasters, all of which are national journals that are searched on the Google Scholar portal using the keyword "Hospital Fire Emergency Planning". Next, the data is analyzed using critical appraisal analysis to examine the core of the journal, reviewing the findings. , and identify similarities and differences between them. From 10 hospital preparedness journals in dealing with fire disasters, it can be seen that several hospital facilities do not meet the specified standards. Identified problems include inadequate fire fighting, inadequate protective facilities, post-disaster procedures, and effectiveness in handling fires in hospitals. There are improvements needed in fire protection systems, employee training, simulations, equipment compliance with guidelines, and proper evacuation route planning. Apart from that, the level of fire fighting capabilities is also considered inadequate in several hospitals.